2017
DOI: 10.1007/s10072-017-3068-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio may be a helpful marker to evaluate disease activity in NMOSD

Abstract: Neutrophil to lymphocyte ratio (NLR) was introduced to assess the activity in autoimmune diseases. Neuromyelitis optica spectrum disorder (NMOSD) has been defined as a chronic inflammatory disease with a course of relapse-remission. Therefore, the relationship between NLR and NMOSD was assessed in this article. Data of NMOSD patients was extracted. NLR is calculated as the absolute count of neutrophil divided by the absolute count of lymphocytes. Correlations between NLR and characteristics of NMOSD patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
1
21
1
1
Order By: Relevance
“…In this study, compared to HC, NLR is higher in LATAM patients with AQP4-ab-positive NMOSD at disease onset. In general, this finding is similar to that previously reported by Lin et al in a cohort of Chinese adult patients ( 17 ). However, we only included NMOSD patients during their first attack and, therefore, all of them were treatment-naïve at disease onset.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, compared to HC, NLR is higher in LATAM patients with AQP4-ab-positive NMOSD at disease onset. In general, this finding is similar to that previously reported by Lin et al in a cohort of Chinese adult patients ( 17 ). However, we only included NMOSD patients during their first attack and, therefore, all of them were treatment-naïve at disease onset.…”
Section: Discussionsupporting
confidence: 92%
“…At that point our analysis seems to indicate that, in AQP4-ab-positive NMOSD, NLR might be a potential surrogate for inflammation and not, strictly speaking, for disease activity ( Table 2 ), contrary to what has been described in previous studies ( 16 , 17 ). As this matter was not entirely clear, our study went one step further and directly assessed the prognostic impact of an abnormally high NRL in LATAM patients with AQP4-ab-positive NMOSD.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…As a marker of systemic inflammation, the NLR is more reliable and stable than the WBC count for reflecting inflammatory responses. The NLR might be a useful marker for assessing the disease activity in neuromyelitis optica spectrum disorder, multiple sclerosis (MS), and systemic lupus erythematosus patients 222324. Our team has recently reported that the NLR is a practical and reliable biomarker for monitoring disease progression in patients with AE 9.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR might be a useful marker for assessing the disease activity in neuromyelitis optica spectrum disorder, multiple sclerosis (MS), and systemic lupus erythematosus patients. [22][23][24] Our team has recently reported that the NLR is a practical and reliable biomarker for monitoring disease progression in patients with AE. 9 In the present study, the NLR was higher in the nonremission group before and after treatment, which may be attributed to the severe inflammatory response and the high probability of pulmonary infection in severe patients.…”
Section: Jcnmentioning
confidence: 99%